2014
DOI: 10.1016/j.devcel.2014.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Hair Follicle Dermal Stem Cells Regenerate the Dermal Sheath, Repopulate the Dermal Papilla, and Modulate Hair Type

Abstract: The dermal papilla (DP) provide instructive signals required to activate epithelial progenitors and initiate hair follicle regeneration. DP cell numbers fluctuate over the hair cycle, and hair loss is associated with gradual depletion/atrophy of DP cells. How DP cell numbers are maintained in healthy follicles remains unclear. We performed in vivo fate mapping of adult hair follicle dermal sheath (DS) cells to determine their lineage relationship with DP and found that a subset of DS cells are retained followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
203
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(216 citation statements)
references
References 27 publications
11
203
1
1
Order By: Relevance
“…Recent work highlighted the developmental origins of mesenchymal fibroblasts and showed that precursors for dWAT and the upper dermal fibroblasts become distinct during development (Driskell et al, 2013). Specialized dermal fibroblasts called dermal papillae provide instructive, growth and regenerative signals for the hair follicle (Chi et al, 2013; Clavel et al, 2012; Jahoda et al, 1984; Rompolas et al, 2012) and may be maintained by fibroblasts in the dermal sheath cell surrounding the hair follicle (Rahmani et al, 2014). Our data provide further evidence for mesenchymal heterogeneity within the dermis by elucidating mechanisms that maintain CD24+ ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work highlighted the developmental origins of mesenchymal fibroblasts and showed that precursors for dWAT and the upper dermal fibroblasts become distinct during development (Driskell et al, 2013). Specialized dermal fibroblasts called dermal papillae provide instructive, growth and regenerative signals for the hair follicle (Chi et al, 2013; Clavel et al, 2012; Jahoda et al, 1984; Rompolas et al, 2012) and may be maintained by fibroblasts in the dermal sheath cell surrounding the hair follicle (Rahmani et al, 2014). Our data provide further evidence for mesenchymal heterogeneity within the dermis by elucidating mechanisms that maintain CD24+ ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is known that e-CAF also induces migration in the human keratinocyte cell line (HaCaT) and primary dermal fibroblasts and human senescent dermal fibroblasts, although no effects on cell proliferation were found; additionally, it produced an improvement in the organization of cytoskeletal proteins F-actin and vimentin and was able to promote the production of ECM components, such as FN and Col I [25]. This study shows that e-CAF could also have beneficial effects on human mesenchymal stem cells from dermal papilla (HHDPCs), improving the capabilities of this cell population, which are of great importance on skin regeneration, because of their multipotential ability to generate different skin lineages [29,30,31,32,33,34,35,36]. In fact, our results showed that treatment with 1 µg/mL of e-CAF for 28 days promoted cell proliferation and 0.1 µg/mL of e-CAF concentrations increased cell migration ability.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, adult mesenchymal stem cells (MSC) have restricted capability to produce a wide range of cell types; it has been proved that they can function as a source of cells for tissue repair, wound healing, and regeneration, maintaining tissue homeostasis [26,27,28]. Human hair dermal papilla cells (HHDPCs) are a specific type of MSCs located at the base of the hair follicle surrounded by the germinal epithelium and involved in its development to produce the hair from the epidermis [29,30]. HHDPCs are not only essential for the development and formation of the hair follicle, but also constitute a reservoir of cells with potential to differentiate into a wide range of cell types, such as muscle cells, adipocytes, fibroblasts and Schwann cells, among others [30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that the DP promotes basal epithelial cell elimination during the regression phase and raised the question of whether DP-mediated regression serves to eliminate either exhausted basal cells or functional cells from an expanded stem cell pool. To test the functionality of the cells eliminated during regression, we devised an experimental setup to transiently remove the mesenchymal DP (Rahmani et al., 2014) during regression and then track the fate of retained cells. Upon DP regeneration, hair follicles were able to fuel a new round of growth from the pool of cells normally targeted for elimination.…”
Section: Main Textmentioning
confidence: 99%